(untitled) (Journal of actual problems of jurisprudence, 2019)
Evaluation of evidence always focused process, the following tasks, which are solved in each stage of the process. Evaluate the evidence may be any actors, but their estimates have different meanings for procedural evidence. In this article the authors examine the concept of the subjects and the evaluation of evidence. Key words: court, prosecutor, defense attorney, investigator, participants in the process, the evaluation of evidence.